2010
DOI: 10.1152/ajpheart.00220.2009
|View full text |Cite
|
Sign up to set email alerts
|

ANG II inhibits insulin-mediated production of PI 3,4,5-trisphosphates via a Ca2+-dependent but PKC-independent pathway in the cardiomyocytes

Abstract: Insulin resistance (IR) is a condition where different organs are refractory to insulin stimulation of glucose uptake. ANG II has been suggested to be involved in the development of IR in the heart. The precise mechanism by which this occurs is still unknown. Here we have used dynamic fluorescent imaging techniques to show that ANG II inhibits insulin production of phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P(3)] in cardiac myocytes. Fluorophore (Venus)-conjugated cAMP-dependent protein kinase-pleckstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To assess cardiac insulin resistance in ANG II-induced hypertrophied hearts, the expressions of phosphorylation of Akt were determined. Akt is an important kinase in the insulin signaling pathway and ANG II can lead to dephosphorylation of Akt and impairment in insulin signaling (9,16). We showed that ANG II was associated with whole-body insulin resistance as determined by the OGTT (Fig.…”
Section: Ang II Induces Cardiac Hypertrophy and Insulin Resistancementioning
confidence: 75%
See 1 more Smart Citation
“…To assess cardiac insulin resistance in ANG II-induced hypertrophied hearts, the expressions of phosphorylation of Akt were determined. Akt is an important kinase in the insulin signaling pathway and ANG II can lead to dephosphorylation of Akt and impairment in insulin signaling (9,16). We showed that ANG II was associated with whole-body insulin resistance as determined by the OGTT (Fig.…”
Section: Ang II Induces Cardiac Hypertrophy and Insulin Resistancementioning
confidence: 75%
“…ANG II-induced myocardial hypertrophy, insulin resistance, and diastolic dysfunction predispose the heart to the development of heart failure (15,26,39) and mimic the LV diastolic dysfunction seen in diabetic cardiomyopathy (3,5). ANG II-induced insulin resistance has been reported in adipocyte, vascular smooth muscle cells, and cardiac myocytes (7,16,22) and is likely due to dephosphorylation and inactivation of Akt (9,16), leading to impairment in insulin signaling.…”
Section: Discussionmentioning
confidence: 99%